Integrated vector management: The Zambian experience - Katebe Cecilia; Sikaala Chadwick; Coleman Michael; Masaninga Fred; Chanda Emmanuel; MacDonald Michael; Baboo Kumar S; Govere John; Manga Lucien (Malaria Journal, 2008)
Abstract Background The Zambian Malaria Control Programme with the Roll Back Malaria (RBM) partners have developed the current National Malaria Strategic Plan (NMSP 2006–2011) which focuses on prevention based on the Integrated Vector Management (IVM) strategy. The introduction and implementation of an IVM strategy was planned in accordance with the World Health Organization (WHO) steps towards IVM implementation namely Introduction Phase, Consolidation Phase and Expansion Phase. Achievements IVM has created commitment for Legal and Regulatory policy review, monitoring, Research and a strong stewardship by the chemical suppliers. It has also leveraged additional resources, improved inter-sectoral collaboration, capacity building and enhanced community participation which facilitated a steady scaling up in coverage and utilisation of key preventive interventions. Thus, markedly reducing malaria incidence and case fatalities in the country. Conclusion Zambia has successfully introduced, consolidated and expanded IVM activities. Resulting in increased coverage and utilization of interventions and markedly reducing malaria-related morbidity and mortality while ensuring a better protection of the environment.